Mapping gender role stress scales utilities: a scoping review approach - Aguilera, Aitana; Villanueva-Moya, Laura; Expósito, Francisca (Frontiers in Psychology, 2024)
Gender role stress emerges as a concept to try to explain the health difficulties presented by men and women due to gender socialization. Thus, gender role stress arises when individuals feel stressed due to their perceived inability to fulfill the demands of their gender role, or when they believe that a particular situation necessitates behavior traditionally attributed to the opposite gender. To evaluate the presence of gender role stress in individuals, two scales were developed: the masculine gender role stress scale and the feminine gender role scale. Objective: To identify the main thematic areas studied in the behavioral sciences with the feminine gender role stress scale (FGRSS) and the masculine gender role stress scale (MGRSS) as main variables, specifically examining their contributions to the understanding of the attitudes and behaviors of individuals who are affected by gender role stress. We also aimed to analyze the difference, both quantitatively and qualitatively, in terms of scientific literature produced between the scales. Method: We followed the preferred items for systematic reviews and meta-analyses (PRISMA) checklist (Tricco et al., 2018). A scoping review of the literature was conducted using systematic techniques, resulting in the inclusion of 87 articles utilizing either of the two scales. Results: 80% (n = 72) of the articles employed the MGRSS, while 20% (n = 18) utilized the FGRSS. The MGRSS articles were also the most frequently cited in the literature. The FGRSS has been predominantly used to examine the implications for women's well-being, whereas the MGRSS has primarily been employed to predict disruptive behaviors in men. Conclusions: This scoping review highlights disparities in the scientific literature concerning the examination of feminine and masculine gender role stress and its consequences for people. Specifically, it points out the limited investigation into feminine gender role stress and its ramifications compared to masculine gender role stress. These findings indicates the lack of a gender perspective even in research intended to study it, and outline the importance of more research with a gender perspective where women are the aim of study.